Experimental and numerical investigation of drainage mechanisms at sports fields under simulated rainfall - Kesgin, Erdal; Agaccioglu, Hayrullah; Dogan, Ahmet (ELSEVIER, 2020)
Infiltration and drainage are complex hydrological considerations to determine unsaturated flow processes in case of irrigation, root growth and pollutant transport in porous media consisting of multi-layered soils. Considering sports fields, this affects the quality of sports organization in terms of player's health, the participation of spectators and the cancellation of games. This study investigated the drainage behavior of sports fields both experimentally and numerically under simulated rainfall. To achieve this goal, a newly-developed experimental setup which consists of a rainfall simulator (RS) that is able to simulate the natural rainfall, and a drainage tank (DT) that is able to pack stratified drainage layers same as in the sports fields were used. Experimental rainfall hyetographs were designed to simulate various rainfall conditions for the relevant region in Istanbul, Turkey. Numerous experiments were conducted to investigate hydrological description of unsaturated flow by using packed drainage layers in the laboratory. Time-dependent water contents were also monitored using soil moisture sensors (10-HS, Decagon Devices) at different depths in the drainage layers. Soil water retention curve (SWRC) of each drainage layer obtained from calibration tests and empirical parameters (a, n) were optimized with HYDRUS-3D model by using water contents and suction pressure results. Observed drain outflow hydrographs were compared with simulated drain outflow hydrographs by using statistical indices of Nash-Sutcliffe Efficiency (NSE) index, Kling and Gupta Efficiency (KGE) index and determination coefficient (R-2). Experimental results and HYDRUS-3D simulations showed good compatibility with the values of NSE, KGE and R-2 varied between 0.859-0.958, 0.594-0.972 and 0.868-0.975, respectively. In the present study, experimental and numerical investigation of the drainage mechanisms for sports fields was evaluated by considering unsaturated flow characteristics through the different drainage layers.
Keywords: Drainage; Sports field; HYDRUS; Rainfall simulator; Hydrograph; Nash-Sutcliffe efficiency; HYDRAULIC CONDUCTIVITY; RUNOFF; WATER; MODEL; Engineering; Geology; Water Resources